Religious, Cultural and Archaeological Significance of Salinadi River Catchment - Maskey, Reshma; Regmi, Smriti (FORESTRY: Journal of Institute of Forestry, Nepal, 2024)
Nepal’s water resources, deeply woven into the cultural, religious, environmental, and social fabric of the nation, are increasingly under threat due to human activity and climate change. These water resources, particularly those in the Kathmandu Valley, hold significant spiritual and historical value, with sacred water bodies central to Hindu and Buddhist rituals, pilgrimages, and festivals. However, rapid urbanization, agricultural expansion, and deforestation have stressed these critical resources, with water quality and availability increasingly compromised. This study focuses on the Salinadi watershed, an area renowned for its cultural and ecological significance, to examine the interrelationship between cultural heritage, land use changes, and water quality. By documenting key religious, archaeological, and environmental sites within the Salinadi catchment, this research assesses three decades of land use and land cover changes and investigates water quality variations along the river, from upstream to downstream. Results indicate a significant transformation in land cover, with urban development causing notable ecological strain, while water quality is deteriorating due to both cultural practices and agricultural runoff. This study highlights the urgent need for integrated conservation strategies that balance the preservation of cultural heritage with sustainable water management, aiming to safeguard both the ecological integrity and spiritual value of the Salinadi watershed.